2017
DOI: 10.1002/acr.22982
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Back Pain in Middle‐Aged Women: Data From the Australian Longitudinal Study of Women's Health

Abstract: Back pain is common in middle-aged women. Increased weight, weight gain, and depression were independent predictors of back pain over 15 years, whereas participation in vigorous physical activity was protective. Targeting these lifestyle factors is an important area for future research on reducing the burden of back pain in middle-aged women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…Seven studies27 29 30 34 41 47 49 defined the levels of physical activity based on frequency of weekly physical activity, five24 35 43 45 51 defined the levels based on number of hours per week, seven3 4 37 39 42 53 57 defined the levels based on number of hours and intensity of activity, four5 7 46 48 defined the levels based on frequency and duration of activity, one31 defined the levels based on frequency and intensity of activity and one56 defined the levels based on frequency, duration and intensity of activity. Moreover, participation in sport or other leisure time physical activities was based on a yes/no question in six studies,33 36 38 40 44 67 which only one36 considered duration and one44 considered intensity of activity.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies27 29 30 34 41 47 49 defined the levels of physical activity based on frequency of weekly physical activity, five24 35 43 45 51 defined the levels based on number of hours per week, seven3 4 37 39 42 53 57 defined the levels based on number of hours and intensity of activity, four5 7 46 48 defined the levels based on frequency and duration of activity, one31 defined the levels based on frequency and intensity of activity and one56 defined the levels based on frequency, duration and intensity of activity. Moreover, participation in sport or other leisure time physical activities was based on a yes/no question in six studies,33 36 38 40 44 67 which only one36 considered duration and one44 considered intensity of activity.…”
Section: Resultsmentioning
confidence: 99%
“…Given that there are few effective treatments for back pain (Maher et al, 2017 ), primary prevention strategies aiming to reduce risk factors for back pain are critical. Obesity is a potential risk factor for the development of back pain (Brady et al, 2017 ); however, it is unclear whether this is due to physical loading on spinal structures or systemic factors. Previous studies have shown that back pain intensity and associated disability are related to increased fat mass, but not muscle mass (Urquhart et al, 2011 ), raising the possibility that there may be systemic factors at play.…”
Section: Introductionmentioning
confidence: 99%
“…Engaging in some forms of physical activity may increase the risk of low back pain (LBP), but in general a physically active lifestyle seems to be protective for LBP 1. The only known effective prevention method is exercise alone or exercise with education 2.…”
mentioning
confidence: 99%